Bestow Pre-Garments Waste Second Life by Converting into a Composite - Hossain, Sajid; Ahtasum, Nafis; Hasan, MD Mahmudul; Jahan, Nusrat; Jim, Monjur E Mowla; Roy, Krishno; Jakaria, Md (Green Engineering Society, 2024)
The pre garments waste consisting of offcuts, trimmings, rejected materials are generated from the garments industry is growing concern nowadays. The recent trend of sustainability practice finds a way to convert this garment waste into composite materials by giving second life. The composites material from garment waste has proven that it is while effective alternative of conventional wood-based materials through the series of mechanical property analysis. The reinforcing garments waste with the help of virgin polypropylene matrix symbolizes the composite material. The amount of fiber reinforcement material and matrix used affects the mechanical and physical characteristics of the composite samples made from textile waste, including tensile strength, elongation, density, and water absorption. The waste-based composite panel board displayed a maximum strength of 31.6 N/mm2, with 40% of its volume taken up by fiber reinforcement components and 60% volume by the matrix. The present study demonstrate that the mechanical and physical characteristics of waste-based composite panel boards are comparable to those of current oriented strand boards and commercial plywood. This waste base composite board can be used for false ceilings, hardboard, wall covering, and fashion purposes also. The results of this study can significantly reduce environmental pollution and offer a practical method for recycling garments waste.